Meanings of ethnic Tetun salvation in the architecture and function of the traditional house of Nonot-Fore Na'in, Malaka Regency, NTT - Koli, Yovendi Mali (Fakultas Ilmu Budaya Universitas Diponegoro, 2023)
Traditional houses play a central role in Tetun ethnic culture. They are not only unique but also serve as a key to understanding various systems of meaning in Tetun ethnicity, including cosmology, anthropology, economics, ethics, politics, and spirituality. The author employs the traditional house's significance to reveal the meaning of salvation in Tetun ethnicity. The research adopts a qualitative method. The author collected information through literature study and interviews. The study revealed similarities between the deep meaning of traditional houses and the concept of salvation in Tetun ethnicity. Specifically, three types of relationships were identified: (1) the relationship between humans, infrahuman beings, and nature, (2) the relationship between humans, and (3) the relationship between humans and the supreme world (spirits, ancestors, and the highest form). The relationships between the Tetun ethnicity, traditional houses, the meaning of salvation, ancestors, spirits, and the supreme being must always be harmonious and go hand in hand. One should not take precedence over the other.